Practical dechlorination of polyvinyl chloride wastes in NaOH/ethylene glycol using an up-scale ball mill reactor and validation by discrete element method simulations - Lu, Jiaqi (Waste management (New York, N.Y.), 2019)
Copyright © 2019 Elsevier Ltd. All rights reserved.